Maggot As an Alternative to Organic Waste Management in Kaliboja Village Pekalongan - M. Iqbal Agil Faiq; Muhammad Alghiffary; Namirotun Sa’diah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Organic waste is one of the environmental problems that must be handled properly and correctly so asnot to cause other problems. This research aims to analyze the problem of organic waste in Kaliboja villagepaninggaran district pekalongan using maggot. This was done for 45 days in kaliboja village. Qualitativemethods are used in this study with data collection techniques in the form of observation, free interviews, anddocumentation. The collected data is tested using the completion method when collecting the data. The result ofthis study is that maggot cultivation can help overcome the problem of organic waste in kaliboja village. Organicwaste is managed by making it as maggot feed or Hermetia illucens.